2020
DOI: 10.1101/2020.04.08.20057539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Use of Adjuvant Therapy in Preventing Progression to Severe Pneumonia in Patients with Coronavirus Disease 2019: A Multicenter Data Analysis

Abstract: medRxiv preprint KEYPOINTS Question: Does the use of adjuvant therapy reduce progression to severe pneumonia in patients with coronavirus disease 2019 (COVID-19)?Findings: In this retrospective, observational cohort study involving 564 patients with confirmed COVID-19, hypertension was an independent risk factor for progression to severe pneumonia irrespective of age and those on angiotensin-converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB) therapy were less likely to develop severe COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 37 publications
(44 reference statements)
2
62
0
Order By: Relevance
“…All of the selected studies were published in 2020 and were all of observational nature 17‐34 . In seven studies, the outcome that matched our research question was death 17,20,21,26‐28,31 ; in two studies, severe pneumonia 23,34 ; in three studies, critical or severe pneumonia 18,19,32 ; in one study, death or critical or severe pneumonia 33 ; in one study, severe pneumonia or death 24 ; and in one study, death, admission to ICU or mechanical ventilation requirement 25 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…All of the selected studies were published in 2020 and were all of observational nature 17‐34 . In seven studies, the outcome that matched our research question was death 17,20,21,26‐28,31 ; in two studies, severe pneumonia 23,34 ; in three studies, critical or severe pneumonia 18,19,32 ; in one study, death or critical or severe pneumonia 33 ; in one study, severe pneumonia or death 24 ; and in one study, death, admission to ICU or mechanical ventilation requirement 25 .…”
Section: Resultsmentioning
confidence: 96%
“…In a qualitative synthesis, seven studies reported a lower risk of the outcome with the use of ACEI/ARB 20,23,27,31‐34 and eleven studies found no association 17‐19,21,22,24‐26,28‐30 …”
Section: Resultsmentioning
confidence: 99%
“…After screening 343 citations, 13 observational studies were included (Figure 1) [18][19][20][21][22][23][24][25][26][27][28][29][30], combining to a total sample of 14,364 participants. The characteristics of included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…diabetes, hypertension, cerebrovascular disease, ischemic heart disease) in the absence of ACEi/ARB drugs. For example, Feng et al showed that hypertension without ACEi/ARB therapy was an independent risk factor for developing severe pneumonia irrespective of age [20].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a multicenter retrospective series of 564 Chinese patient, hypertension without receiving ACEI/ARB therapy was an independent risk factor (odds ratio [OR], 2.07; 95% CI, 1.07 to 4.00) for developing severe pneumonia irrespective of age [56].…”
Section: Therapeutic Opportunities Targeting the Ras System In Covid-19mentioning
confidence: 99%